Analyzing Customers' Switching Intentions in the Telecom Sector. Issue 3 (26th May 2016) - Kaur Sahi, Gurjeet; Sambyal, Ritika; Sekhon, Harjit Singh
ABSTRACT: Mobile Number Portability (MNP) has not only affected customers' behavioral patterns, but also increased competition among telecom operators. Against this backdrop, the study examines the relationship between customers' switching intentions and attitude towards MNP, customer loyalty, and switching barriers. It also investigates the impact of these intentions on actual switching or staying behavior of customers. Data were collected from a sample of 260 telecom customers comprising university students. Findings reveal that customers' switching intentions would largely depend upon switching barriers perceived by them. Switching intentions predict both actual staying and switching behavior. Our understanding of switching barriers is limited to those involved in switching from a current service provider to a new service provider. Future research can examine the barriers associated with returning to the original provider and the effect on the decision to leave in the first place, especially in the case of contractual agreements such as BSNL. The present study will help practitioners and telecom service providers in understanding the factors affecting customers' switching intentions to prevent switching.